Selective Autophagy of Mitochondria on a Ubiquitin-Endoplasmic-Reticulum Platform - Zachari, Maria; Gudmundsson, Sigurdur R; Li, Ziyue; Manifava, Maria; Cugliandolo, Fiorella; Shah, Ronak; Smith, Matthew; Stronge, James; Karanasios, Eleftherios; Piunti, Caterina; Kishi-Itakura, Chieko; Vihinen, Helena; et al. (Developmental cell, 2019)
The dynamics and coordination between autophagy machinery and selective receptors during mitophagy are unknown. Also unknown is whether mitophagy depends on pre-existing membranes or is triggered on the surface of damaged mitochondria. Using a ubiquitin-dependent mitophagy inducer, the lactone ivermectin, we have combined genetic and imaging experiments to address these questions. Ubiquitination of mitochondrial fragments is required the earliest, followed by auto-phosphorylation of TBK1. Next, early essential autophagy proteins FIP200 and ATG13 act at different steps, whereas ULK1 and ULK2 are dispensable. Receptors act temporally and mechanistically upstream of ATG13 but downstream of FIP200. The VPS34 complex functions at the omegasome step. ATG13 and optineurin target mitochondria in a discontinuous oscillatory way, suggesting multiple initiation events. Targeted ubiquitinated mitochondria are cradled by endoplasmic reticulum (ER) strands even without functional autophagy machinery and mitophagy adaptors. We propose that damaged mitochondria are ubiquitinated and dynamically encased in ER strands, providing platforms for formation of the mitophagosomes.